Epidemiological Characteristics of Hand, Foot, and Mouth Dis-ease Outbreaks in Qingdao, 2009-2018 - Jing Jia; Fei Kong; Xueling Xin; Jiwei Liang; Hualei Xin; Liyan Dong; Fachun Jiang (Tehran University of Medical Sciences, 2021)
Background: In China, hand, foot, and mouth disease (HFMD) outbreaks have become an important issue recent years. We analyzed the epidemiological characteristics of HFMD outbreaks in Qingdao during 2009-2018, and provided evidences for prevention and control of the disease. Methods: Data were analyzed by descriptive analysis and correlation analysis, and throat swabs were detected for enterovirus RNA using RT-PCR. Results: Overall, 116 HFMD outbreaks were reported in Qingdao during 2009-2018, with the epidemic of the outbreaks exhibiting a decreasing tendency. The characteristics of outbreaks presented two patterns, including two-peak pattern and rural area to urban-rural fringe area to urban areas pattern. Male patients were predominant in these outbreaks. The location of the outbreaks changed from nursery to community. Non-EV71/CA16 enteroviruses were gradually becoming predominant enteroviruses serotypes. The durations of outbreaks were positively correlated with response times and the number of cases. Conclusion: The epidemiological characteristics analysis of HFMD outbreaks could provide a scientific basis for the prevention and control the disease. Reporting and handling promptly are the keys to control epidemic outbreaks of HFMD.